'An African Representative': Canada, the Third World, and South African Apartheid, 1984–1990. Issue 2 (4th March 2021) - Manulak, Daniel
ABSTRACT: South African apartheid served as a battleground between East and West, and North and South, but it was also an issue that gave coherence to an often disparate Third World political project. And, though it has rarely been appreciated by historians, apartheid exposed and deepened fault lines between allies. This article addresses this oversight by exploring why, during the mid 1980s, Canada became so engaged on a file that was seemingly peripheral to its national interests. Drawing on recently declassified Canadian, British, and South African documents, and on interviews with former policymakers, officials, and activists, it shows how Canada became a diplomatic battleground in the fight for legitimacy between Pretoria and the opponents of apartheid. These entanglements shaped public discourses and, in turn, informed Canadian policy towards apartheid. For Canada, the issue was not solely about the East–West conflict but a deeper struggle to maintain the credibility of the liberal world order. This paper thus offers an 'outside-in' vantage point to the international history of the Commonwealth and a window to understand global dynamics, priorities, and norms beyond the Cold War paradigm.